(untitled) (Journal of Contemporary Philology, 2026)
The form of socialism introduced in Yugoslavia after the Second World War under Josip Broz Tito is still being discussed from many contrasting viewpoints in the territory of former Yugoslavia. In the context of such discussions, Elena Filipovska published the novel Идол на ѕидот (Idol on the Wall, 2020). The story is set in modern-day Skopje, but in an alternative history in which Yugoslavia did not disintegrate. Instead, a third marshal leads the country, continuing and transforming the socialist rule into an increasingly dehumanized variant. This article explores how the novel constructs a dystopia, which both resembles life in the past, specifically in the 1970s and 1980s, and is based on familiar tropes in dystopian fiction: removal of children from their parents’ care to be raised by the state, fear of being followed by the government intelligence service, and nationalization of private property. The novel has mainly been discussed as criticism of the socialist system. I argue, however, that the ideas expressed through the narrative are much more ambiguous, and that rather than being critical, the novel assumes a more complex position toward socialist legacy.